Prophetischer oder marxistischer Sozialismus? - Max Scheler (Дискурс, 2021)
German philosopher and sociologist Max Scheler (1874–1928) puts forward the concept of “prophetic Christian socialism” as a means of political and ideological opposition to Marxism. The concept expresses his religious-philosophical views, developed in earlier works, primarily in the main work “Formalism in Ethics and Material Ethics of Values”. Scheler compares his own views on socialism, understanding of history, the possibility of foreseeing historical processes with the views of these realities of K. Marx. Scheler's criticism of Marx's teachings is interspersed with the recognition of its partial correctness.